(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
W.F. Skene discussed a number of manuscripts which had been associated with the legend of the Red Book of Clanranald. One was the manuscript given to James MacPherson, who later went on to publish what he called fragments of poetry by Ossian, allegedly ancient Gaelic in origin. By analyzing the history of the various manuscripts that he had collected, Mr. Skene cast doubt on MacPherson’s claims. Skene gives notice of his intent to deposit the various manuscripts in the Advocates’ Library.